Management system of islamic private secondary schools in Bangkok, Thailand - Kornkasem, Jeeranan; Salleh, Mohamad Johdi (2010)
This study discusses the establishment of Islamic Private Secondary Schools in Bangkok and the schools’ management system which comprises of the organizational structure, school finance, school physical facilities, teaching staff and parents’ involvement in the school. This study will also identify some problems and obstacles that inhibit the effectiveness of the schools, and followed by suggestions to improve the schools toward the betterment. The data were collected through library research, interview with the headmasters and teachers in the schools, and, direct observation. The findings of the study show that the growth of Islamic private schools in Bangkok was a continuation of the Pondok institution which had developed throughout the years formerly from Pattani. The aims of these schools were to produce God conscious people with exemplary moral characters based on the Quran and Prophetic tradition, and, producing students who can apply knowledge in real life and preaching it to others. However, the principals’ perception of the problems faced by the Islamic Private Secondary Schools in Bangkok referred to various problems such as financial problem, lack of government support, and, lack of parent commitment. Finally, the researcher provides relevant suggestions to improve the schools betterment and enhance students’ achievement.